FUNCTIONAL AND PRAGMATIC ROLES OF PROVERBS IN ENGLISH AND GERMAN DISCOURSE COMMUNITIES - Shukurov Abbos Gulomovich; Olimov Avazbek Tursunpo’lot o’g’li (TADQIQOTLAR, 2025)
Annotation: This article explores the functional and pragmatic roles of proverbs in  English  and  German  discourse  communities.  Proverbs,  as  culturally  embedded linguistic units, serve not only as carriers of collective wisdom but also as tools for persuasion, social regulation, and identity expression. The study analyzes how English and  German  speakers  employ  proverbs  in  everyday  communication,  institutional discourse,  media,  and  literature.  Attention  is  given  to  the  pragmatic  functions  of proverbs  such  as  argumentation,  mitigation,  strengthening  claims,  and  establishing social solidarity. By comparing their use across the two linguistic and cultural contexts, the article highlights similarities rooted in shared European cultural heritage as well as differences  influenced  by  historical,  social,  and  cognitive  factors.  The  findings contribute to a deeper understanding of how proverbs shape interpersonal interaction and cultural communication patterns.